Condition of Service and Employees Attitude in Rivers State University - Kabari, John Baribor (Researchparks Publishing, 2021)
Staff wellbeing is a critical problem in every organisation and should not be taken lightly. This is because employees play a critical part in the production process of any firm, and as such, if their welfare is neglected (if their working conditions are substandard), it might impact their attitude at work. As such, the research investigated the state of service and employee attitudes at Rivers State University. The study's focus is confined to Rivers State University's non-teaching employees. Three study objectives and three associated research questions served as the framework for the article. The Maslow and Herzberg theories of motivation were used to support the study. A descriptive survey design was used in this investigation. This research involved all non-teaching personnel at Rivers State University. The institution employs nine hundred and seventy-three (973) teaching and non-teaching staff. The Taro Yamane Formula was used to generate a sample of 324 individuals from staff of Rivers State University. The data collecting tool was a questionnaire devised by the researcher named 'Condition of Service and Employees' Attitude Questionnaire' (CSEAQ). The CSEAQ was developed using a four-point rating scale. The mean and standard deviation were used to analyse the data at 2.50 which serves as the basis for decision-making. The data indicated that leave bonuses, training allowances, a positive work environment, and promotions all have a significant impact on employee attitudes at Rivers State University. The investigation concluded, among other things, that personnel at Rivers State University should be promoted in accordance with established procedures. This enables them to maintain a favourable attitude toward their career.